2019
DOI: 10.1002/admi.201900678
|View full text |Cite
|
Sign up to set email alerts
|

Progress Report on Atomic Layer Deposition Toward Hybrid Nanocomposite Electrodes for Next Generation Supercapacitors

Abstract: In present supercapacitors' research atomic layer deposition (ALD) has proven to be a better technique of choice since the controlled deposition and better conformal surface coating minimize the ion diffusion and charge transport path which result in a supercapacitor with optimized energy and power density, good cyclic stability, and rate capability. This progress report summarizes the recent advances in ALD toward fabrication and surface modification of advanced hybrid nanocomposite electrodes for supercapaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 145 publications
0
18
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28] Recently, ALD has been explored as a fabrication technique for the preparation of various active materials on a highly porous substrate for application in fields such as Li-ion batteries and supercapacitor. [29][30][31][32][33] However, the deposition of MoN x on CC or NCCC has not been reported and studied as a catalyst for HER. The self-limiting growth kinetics, the linearity of growth with ALD cycles and the temperature window for ALD-MoN x using Mo(CO) 6 and NH 3 has been previously established by our group: The results indicated that the ideal ALD conditions occurs only in a very narrow temperature range of 200-215 8C on a SiO 2 /Si substrate.…”
Section: Ald Of Monmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] Recently, ALD has been explored as a fabrication technique for the preparation of various active materials on a highly porous substrate for application in fields such as Li-ion batteries and supercapacitor. [29][30][31][32][33] However, the deposition of MoN x on CC or NCCC has not been reported and studied as a catalyst for HER. The self-limiting growth kinetics, the linearity of growth with ALD cycles and the temperature window for ALD-MoN x using Mo(CO) 6 and NH 3 has been previously established by our group: The results indicated that the ideal ALD conditions occurs only in a very narrow temperature range of 200-215 8C on a SiO 2 /Si substrate.…”
Section: Ald Of Monmentioning
confidence: 99%
“…Full-stack ASTBs have thicknesses of only ∼10-15 μm including current collectors, electrolyte, and electrodes, yet the substrate thickness at least doubles the overall battery thickness (Dudney 2008). Thin-film electrodes manufactured by physical vapor deposition (PVD), chemical vapor deposition (CVD), and atomic layer deposition (ALD) are recognized as pure materials since they do not have binders or conductive materials as in conventional powder slurry technology (Dasgupta et al, 2015;Kozen et al, 2015;Xie et al, 2017;Gandla and Tan 2019;Lidor-Shalev et al, 2019). However, large breakdowns in electrochemical efficiency are still noticeable for electrode components, electrolytes, and electrode-electrolyte interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[ [26]. It was concluded that ALD parameters play a vital role in ZnO formation and subsequently on the recorded electrochemical properties [27,28].…”
Section: Introductionmentioning
confidence: 99%